Antidiabetic activity of aqueous extract of leptospermum flavescens in alloxan induced diabetic rats - Asmawati Abd. Rahim,; Jamaludin Mohamad,; Zazali Alias, (Universiti Kebangsaan Malaysia, 2014)
Leptospermum flavescens, commonly known as ‘Gelam bukit’ has been used by the Malays as traditional plants in Malaysia for antidiabetic treatment. However, at this moment there is no scientific evidence and data available to validate such claim. In the present study, the aqueous extract of leaves and stems were studied for its antidiabetic activity. The total phenols and flavonoids were determined and correlated with antidiabetic activity. The detection of aqueous leaves extract with LCMS/MS showed the presence of flavonoids aromadendrin glucoside, kaempferol rhamnoside, quercetin rhamnoside and vindoline. The extract has significantly inhibited glycogen phosphorylase at 85% with IC50 = 0.18 mg/mL. In the alloxan induced diabetic rats showed that extract at 500 mg/kg decreased significantly fasting plasma glucose level by 61.9% (p<0.001) on the 20th day as compared to diabetic control. The treatment with Leptospermum flavescens at 500 mg/kg showed that it decreased the total cholesterol and triglycerides but restored the HDL level. The high antidiabetic activity was correlated with high total phenol at 1.57±0.01 GAE/g and total flavonoids at 1.41±0.01 mg QE/g. Thus, the high antidiabetic activity of the aqueous leaves extract attributed due to the presence of aromadendron glucoside, kaempferol rhamnoside, quercetin rhamnoside and vindoline in aqueous extract of Leptospermum flavescens.